2010
DOI: 10.1016/j.spinee.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of adenovirus-mediated growth and differentiation factor-5 in a mice disc degeneration model induced by annulus needle puncture

Abstract: BACKGROUND CONTEXT-The therapeutic strategies that have thus far been employed for the treatment of intervertebral disc degeneration (IDD) have focused on relieving the symptoms, while reversal of the degeneration remains an important challenge for the effective treatment of IDD. Growth and differentiation factor-5 (GDF5), of which deficiency leads to early disc degeneration changes, has the potential to increase proliferation of disc cells and expression of extracellular matrix proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 40 publications
1
73
0
Order By: Relevance
“…Consistent with previous reports, Ad-GDF-5 treatment not only promotes the expression of ECM proteins but also could improve the construction and function of NP cells in vivo via the sustained transcription and translation of ECM proteins (Wang et al, 2004;Feng et al, 2008;Liang et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports, Ad-GDF-5 treatment not only promotes the expression of ECM proteins but also could improve the construction and function of NP cells in vivo via the sustained transcription and translation of ECM proteins (Wang et al, 2004;Feng et al, 2008;Liang et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The results not only confirmed the longterm expression of the target protein in the disc in vivo, but also highlighted the physiological improvements that occurred to the disc. Ad-GDF-5 gene therapy could restore the functions of injured discs and has the potential to be an effective treatment (Liang et al, 2010). In other research GDF-5 was transfected with mesenchymal stem cells (MSCs) by electroporation to prepare the seed cells for IVD cell therapy (Bucher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Thus, GDF5 gene deficiency, mutation, or abnormal expression can cause variable changes in cell growth and ECM synthesis and promote the development of IDD. Increasing evidence suggests that GDF5 aids in maintaining the structural integrity of the IVD and effectively restores disc physiological function, thereby delaying or even reversing IDD.…”
Section: Discussionmentioning
confidence: 99%
“…GDF5 protein treatment augmented anabolic metabolism of disc cells from either GDF5 deficient mice or wild-type mice. Intra-disc injection experiments also showed that the administration of GDF5 promotes inner AF cells migrating to injured NP area and presenting chondrogenic phenotype [81].…”
Section: Af Cells Response To Different Stimulimentioning
confidence: 93%